(untitled) (Ibrahim Medical College Journal, 2013)
Maternal mortality is an important indicator which reflects the health status of a community. It can be calculated by maternal mortality ratio (MMR), maternal mortality rate (MMRate), and adult life time risk of maternal death. MMR estimates are based on varieties of methods that include household surveys, sisterhood methods, reproductive-age mortality studies (RAMOS), verbal autopsies and censuses. Main causes of maternal mortality are hemorrhage, infection, unsafe abortion, hypertensive disorder of pregnancy and obstructed labour. Factors of maternal mortality have been conceptualized by three delays model. Estimates of maternal mortality ratio (MMR) trend between 1990 and 2010 (over 20 years period) suggest a global reduction (47%), with a greater reduction in developing countries (47%) including Bangladesh than in developed countries (39%). However, to meet the challenge of Fifth Millennium Development Goal (MDG5 i.e. to ensure 75% reduction of MMR by the year 2015), the annual rate of MMR decline and increase of skilled attendant at birth need to be still faster. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14735 Ibrahim Med. Coll. J. 2012; 6(2): 64-69